Protocol for a systematic review of reporting standards of lower limb endovascular interventions in peripheral arterial disease - Ewa M. Zywicka; Lucy Elliott; Christopher P. Twine; Ronelle Mouton; Robert J. Hinchliffe (Systematic Reviews, 2023)
Abstract Introduction Techniques and devices for the endovascular treatment of peripheral arterial disease (PAD) are continuously evolving. High-quality clinical trials limit the variation in how endovascular interventions are described, performed and reported. The aim of this systematic review is to assess the quality of reporting standards in randomised controlled trials (RCTs) of endovascular lower limb interventions against the Consolidated Standards of Reporting Trials for Non-Pharmacologic Treatments (CONSORT-NPT) and template for intervention description and replication (TIDieR) framework. Methods Randomised trials including participants with peripheral arterial disease undergoing any infra-inguinal lower limb endovascular arterial intervention, searched from Medline, Embase and Cochrane Library databases from inception to December 2021, will be included. All study data, including details of the procedure investigated, will be extracted in keeping with the CONSORT-NPT and TIDieR checklist. Descriptive statistics will be used to summarise general study details and reporting standards of the trials. Discussion The results will be used to inform the design of future RCTs in this area by optimising the way the interventions are described, standardised, and monitored. The systematic review will be disseminated via peer-reviewed manuscripts and presentations at relevant conferences. Systematic review registration PROSPERO CRD42022288214